Community Empowerment Based on Creative Economy Through Training on Making Siwalan Sticks (Stikland) in Gaji Village, Kerek District, Tuban Regency - Inarotul A’yun; M. Yusuf Aminuddin (Shof Literacy Community, 2024)
Community empowerment is one form of increasing human resource development. In this case, it is related to the creative economy, which is to try to hone community innovation towards better development and to be able to compete in the economic market. This research uses a qualitative descriptive method with field research. Training participants will receive practical learning about traditional siwalan stick-making techniques and an understanding of the business aspects. The results of this program are expected to include improving the skills of participants, the establishment of several small and medium enterprises (UKM) engaged in the production and marketing of siwalan sticks, as well as increasing public interest in creative siwalan stick products as local products with high cultural value. It is hoped that this collaboration program can contribute to improving the welfare of the community in Gaji Village and driving creative economic growth based on local potential in the Kerek District area, Tuban Regency